Strategi Branding Image Dalam Meningkatkan Daya Saing Pendidikan di SMAN 1 Badegan - Desi Nur Fitriningsih; Mukhibat (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
Educational institutions are currently competing in the formation of a good brand image in order to attract the interest of the public / new students, with this being able to increase the competitiveness of education. So educational institutions must be able to develop their own brand by coming up with new innovations to find ideas in improving the brand so that it can be competitive between institutions, as well as attracting interest from the community and forming a brand name that sticks in the minds of the community. This study used qualitative methods with descriptive research types, data collection techniques in the form of interviews, observation, and documentation. The results of the research on the concept of branding from SMAN 1 Badegan are that the school has efforts to advance the institution and meet community needs by forming branding that is acceptable to the community. (1) Form a branding image strategy with consistency and collaboration related to the brand that is owned, namely essay schools, double track, tahfidz, and child-friendly schools (2) Implementation of branding image strategies through positioning by positioning the school brand so that it can be known by the public, has brand values by introducing the brand through social media, and having the right concept by increasing the school's brand through student achievement by means of intensive coaching. (3) the implications of its application are by increasing the interest of new students, creating quality graduates, and providing an identity for schools.